2002
DOI: 10.1070/rc2002v071n08abeh000728
|View full text |Cite
|
Sign up to set email alerts
|

Complex phosphates containing mono- and trivalent cations

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…In this context, complex phosphates containing mono-and trivalent cations are of particular interest [1][2][3]. The structural properties of these compounds were discussed in detail and it was revealed that the sizes of the M I and M III cations and their ratio have a dominant role in their structure formation [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, complex phosphates containing mono-and trivalent cations are of particular interest [1][2][3]. The structural properties of these compounds were discussed in detail and it was revealed that the sizes of the M I and M III cations and their ratio have a dominant role in their structure formation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have been systematically studying the reactivity of alkali and ammonium cations in hydrothermal synthesis and the crystal chemistry of complex gallium and indium phosphates without¯uoride agents Zhizhin et al, 2000;Filaretov et al, 2006;Rusakov et al, 2006) and with¯uoride ions as templates (Filaretov, Zhizhin, Olenev et al, 2002;Komissarova et al, 2002). In this context, we report here the hydrothermal synthesis and characterization of the ®rst potassium gallium hydrogenphosphate¯uoride, K 2 Ga[H(HPO 4 ) 2 ]F 2 , (I).…”
Section: Commentmentioning
confidence: 98%
“…We originally began investigating the growth of vanadates as building blocks in optical applications, particularly in their role as laser hosts or luminescent materials. The vanadates play a much broader role as a structural building block unit, however. Specifically, they are a member of the class of tetrahedral oxyanions (e.g., PO 4 3– , SO 4 2– , MoO 4 2– ) that display extensive structural versatility and can link both d-block and rare earth metal ions in a variety of environments. , The tetrahedral building blocks can play particularly interesting roles in magnetic solids since they can bridge in multiple environments to generate extended chains, three-dimensional frameworks, or two-dimensional lattices, including those with threefold symmetry leading to spin-frustrated systems with interesting and important magnetic properties …”
Section: Introductionmentioning
confidence: 99%